Development and evaluation of selective nitroxanthone derivatives: a promising compound for targeting MCF-7 breast cancer cells - Devakrishnan, Pavithren; Mad Nasir, Nadiah; Stanslas, Johnson; M. Latif, Muhammad Alif; Ismail, Ahmad Zaidi; Baharuddin, Fatin Farhana (Elsevier B.V., 2025)
A series of nitroxanthone derivatives (1–6) were synthesized and evaluated for their potential efficacy against estrogen-receptor positive (MCF-7) and triple-negative breast cancer cell lines (MDA-MB-231). Cell viability assays identified compound 1 at 10 µM as the most promising candidate due to its potent growth inhibitory activity (22.05 ± 2.40 %) against the MCF-7 cell line. The half-maximal inhibitory concentration (IC50) of compound 1 was 7.00 ± 0.00 µM for MCF-7 cells, compared to 250.00 ± 70.71 µM for HaCaT and 800.00 ± 0.00 µM for RAW 264.7 cells, yielding selectivity indices (SI) of 35.71 and 114.29, respectively. Additionally, compound 1 exhibited mortality concentrations of 1736.58 µM and 3660.35 µM for zebrafish and brine shrimp embryos, with SI values of 522.91 and 248.08, respectively. Molecular docking analysis showed that compound 1 binds more efficiently to the target enzyme aromatase compared to other derivatives, likely due to its optimal number of nitro groups, orientations, and polarizabilities. Crystal structure analysis revealed that compound 1 crystallizes in the monoclinic system with the C2/c space group. In summary, compound 1 demonstrates selective toxicity towards tumor cells (MCF-7) while being non-toxic to normal cell lines (HaCaT and RAW 264.7) and in vivo studies with brine shrimp and zebrafish. These findings suggest that compound 1 holds promise as a lead compound to target breast cancer cells.